Same same but different [videorecording (DVD)] - Kross, David, 1990-; Sakuljaroensuk, Apinya ([Publisher not identified], 2014)
Revolves around Ben, a young German student traveling to Cambodia on a post-graduation summer trip, and Sreykeo, a 21-year-old bar girl in Phnom Penh. The two meet in a nightclub and quickly fall in love. After Ben returns home to Germany, Sreykeo, skyping from Cambodia, reveals that she is HIV-positive.